2018
DOI: 10.1097/md.0000000000010798
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of multiple refractory ankle ulcerations in thromboangiitis obliterans

Abstract: Rationale:Thromboangiitis obliterans (TAOs, or Buerger's disease) present as a non-atherosclerotic segmental occlusive vasculitis within medium- and small-sized blood vessels. TAO frequently occurs in young adults and is associated with cigarette smoking. At present, there are no accurately defined treatments for TAO.Patient concerns:A 34-year-old Asian woman with a 20-year history of heavy cigarette smoking and recurrent, small, and self-limited lower limb ulcerations since adolescence, presented with persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Thus, omalizumab, as an anti-IgE can be beneficial for the treatment of TAO. 33 In another study, levels of all serum Igs showed a significant rise in TAO patients as compared with controls. 34 This finding was also supported by the findings of Gulati et al 35 Garc ıa et al reported a significant increase in IgA levels of patients with Buerger's disease.…”
Section: Variablesmentioning
confidence: 89%
“…Thus, omalizumab, as an anti-IgE can be beneficial for the treatment of TAO. 33 In another study, levels of all serum Igs showed a significant rise in TAO patients as compared with controls. 34 This finding was also supported by the findings of Gulati et al 35 Garc ıa et al reported a significant increase in IgA levels of patients with Buerger's disease.…”
Section: Variablesmentioning
confidence: 89%
“…Thromboangiitis obliterans (TAO) is a chronic occlusive disease characterized by segmental, non-suppurative inflammation, and intravascular thrombus formation (1). It mainly invades the limbs, especially the small and medium arteries and veins of the lower limbs, and then causes ischemic changes in the distal side of the affected limb (2). At present, TAO mainly presents as limb ischemia, pain, intermittent claudication, migrating phlebitis, extremity gangrene, secondary infection, and even disability (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…The immune system and inflammatory response play an important role in the pathogenesis of TAO. The interaction between inflammation and hemostasis increases the tendency of thrombosis, and chronic inflammation can induce endothelial damage ( 12 ). Vascular endothelial growth factor (VEGF) is an endogenous angiogenic growth factor that acts on vascular endothelial cells and promotes vascular growth and endothelial proliferation ( 13 ).…”
Section: Introductionmentioning
confidence: 99%